2021
DOI: 10.31235/osf.io/wm2p3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migrant Selection and Sorting during the Great American Drought

Abstract: Migration is among the most basic adaptation methods to inhospitable environments and has large economic consequences for both migrants and the broader economy. To estimate the impact of the worst drought in U.S. history on migration, I match 1940 census data with county-level drought conditions. I find that drought substantially increased migration rates for individuals with a 12th grade education or higher but had little impact on migration rates for people with less education. This differential migration re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…short-term and short-distance internal migration-much like the well documented but short-lived stream of internal refugees in the wake of the Messina-Reggio Calabria Earthquake (e.g., Gray and Mueller 2012;Gröger and Zylberberg 2016;Penning-Rowsell et al 2013;Robalino et al 2015)-and permanent longdistance internal migration (Boustan et al 2012;Hornbeck 2012;Hornbeck and Naidu 2014;Sichko 2021). Some studies have also found similar positive effects on international migration (e.g., Drabo and Mbaye 2014;Reuveny and Moore 2009).…”
Section: Natural Disasters and Migration: Theory And Evidencementioning
confidence: 88%
See 1 more Smart Citation
“…short-term and short-distance internal migration-much like the well documented but short-lived stream of internal refugees in the wake of the Messina-Reggio Calabria Earthquake (e.g., Gray and Mueller 2012;Gröger and Zylberberg 2016;Penning-Rowsell et al 2013;Robalino et al 2015)-and permanent longdistance internal migration (Boustan et al 2012;Hornbeck 2012;Hornbeck and Naidu 2014;Sichko 2021). Some studies have also found similar positive effects on international migration (e.g., Drabo and Mbaye 2014;Reuveny and Moore 2009).…”
Section: Natural Disasters and Migration: Theory And Evidencementioning
confidence: 88%
“…This frequently observed lack of a positive effect of shocks on migration gives rise to the notions of trapped populations (Nawrotzki and DeWaard 2018) and an immobility paradox (Beine et al 2019), describing a state in which poor populations would have wanted to react through migration, but are locked in by liquidity constraints that are exacerbated by the shock. Findings of heterogeneous effects of shocks on migration with respect to income, wealth, or human capital, and with a greater increase in migration after a shock among better-off households, regions, or countries (Beine and Parsons 2017;Cattaneo and Peri 2016;Gröschl and Steinwachs 2017;Nawrotzki and DeWaard 2018;Sichko 2021;c.f., Halliday 2006) are consistent with such a mechanism.…”
Section: Natural Disasters and Migration: Theory And Evidencementioning
confidence: 99%
“…This paper thus adds to these studies, building on them by providing information for immigrants during the Age of Mass Migration and comparing their patterns to those of natives. It most closely complements Zimran's (2021) linked data-based analysis of natives' internal migration in the period 1850-1940, as well as the studies of the rates, selection, and sorting of specific episodes of historic US internal migration (e.g., Collins and Wanamaker 2015;Hornbeck 2020;Sichko 2021;Stewart 2006).…”
Section: Introductionmentioning
confidence: 80%
“…The drought had devastating consequences including towering dust storms fueled by "the Great Plow Up" and widespread, repeated, crop failures throughout the region. Many farmers abandoned their property during the 1930s in a mass environmental migration (Hornbeck, 2020;Long & Siu, 2018;Sichko, 2021). Nonetheless, most people stayed and more sustainable agricultural practices (subsidized and orchestrated by the U.S. Department of Agriculture, including the Soil Conservation Service) took hold starting in the mid-1930s (Cunfer, 2005).…”
Section: Homesteading and The Uncertainties Of Agriculture On The Gre...mentioning
confidence: 99%
“…At the same time, a drought that would persist through 1939 swept across the United States (Sichko, 2021). Non‐coincidentally, the drought centered on the semi‐arid and drought‐prone Great Plains, then populated by millions of homesteaders.…”
Section: Homesteading and The Uncertainties Of Agriculture On The Gre...mentioning
confidence: 99%